Fostering Parasocial Relationships with Celebrities on Social Media: Implications for Celebrity Endorsement. Issue 4 (April 2017) - Chung, Siyoung; Cho, Hichang
ABSTRACT: The purpose of this study was to explore the underlying mechanisms through which the use of social media affects endorser effectiveness. Based on theories related to parasocial relationships, self‐disclosure, and celebrity endorsement, this study proposed a theoretical research model and empirically tested the model using online survey data collected from 400 Korean Wave fans in Singapore. The results showed that consumers' parasocial interactions with celebrities though social media have a positive impact on celebrity endorsement. Specifically, we found that: (1) parasocial relationships mediated the relationships between social media interactions and source trustworthiness, (2) social media interactions influenced parasocial relationships via self‐disclosure; and (3) source trustworthiness had a positive effect on brand credibility, which, in turn, led to purchase intention. Implications for research and practice are discussed.